Sarbanes-Oxley and the board of directors : - Green, Scott (John Wiley & Sons, 2005)
Well-aware of the fact that the boards of Enron and WorldCom met criteria for acceptable governance practices, a lawyer ventures beyond the management concerns he discussed in his Manager's Guide to the Sarbanes-Oxley Act (Wiley, 2004) to address the Act's broader implications for governance in US businesses. Green traces US regulatory history from the 19th century up to this 2002 act targeting public company financial reporting. He includes recommendations; case studies; companies rated high/low for their governance practices; examples of well-known companies' principles for governance; and a board self-assessment tool.